RESHAPING BANKING: THE USE OF CHATBOTS FOR CUSTOMER SERVICES - Nurul Afidah Mohamad Yusof; Anthonysamy, Lilian; Wan Rozima Mior Ahmed Shahimi; Tun-Pin, Chong; Kogilavani Apadore (International Journal of Accounting, Finance and Business, 2023)
The use of digital technology in the banking sector has been crucial now more than ever. To achieve competitive advantage, banks have been fast to adopt digital strategies to transform their customer experience. The objective of this study is to examine the factors influencing bank customers’ intention to use chatbot for their banking customer service solution. This study extended the use of UTAUT by analysing the antecedents to its four main elements based on the stages of the launch of new technology products. By using questionnaires, data from 136 respondents were collected and analysed using structural equation modelling (SEM). Findings revealed that the four stages of new technology launch (market preparation, targeting, positioning execution) are significant antecedents to the UTAUT variables in examining the factors influencing the intention to use chatbot for banking customer service. In addition, the results indicated that performance expectancy, effort expectancy, and social influence have a significant influence on behavioural intention. Therefore, banks should carefully consider all these factors during the development of chatbot system for their customer service solutions.